Perancangan dan Pembuatan Aplikasi Media Pembelajaran Berbasis Android pada Mata Pelajaran Produk Kreatif dan Kewirausahaan - N Nurhayati; Yuliawati Yunus; Astri Indah Juwita (Universitas Putra Indonesia YPTK Padang, 2021)
This study aims to determine the validity, practicality and effectiveness of designing and making Android-based learning media applications in the subject of Creative Products and Entrepreneurship for Class XII TKJ 2 at SMK Negeri 8 Padang Odd Semester, Academic Year 2020/2021. This study uses a research development method (research & Development). The research subjects were 35 people. The research model used is the development research model (ADDIE model), with the design of the development steps as follows. (1) Analyze, (2) Design, (3) Development, (4) Implementation and (5) Evaluate. The results of the validity test by the experts as a whole validator test assessment of Android-Based Learning Media Applications in the subject of Creative Products and Entrepreneurship Class XII TKJ 2 SMKN 8 Padang amounting to Odd Semester 82.20%, so that the level of validity can be interpreted as valid to use. The results of the overall practicality test assessment of the practicality of Android-Based Learning Media Applications in the subject of Creative Products and Entrepreneurship Class XII TKJ 2 SMKN 8 Padang Odd Semester is 90.79%, so that the level of practicality can be interpreted as Very Practical to use. The results of the overall effectiveness test assessment of the effectiveness of the Android-Based Learning Media Application in the subject of Creative Products and Entrepreneurship Class XII TKJ 2 SMKN 8 Padang Odd Semester is 84.91%, so that the level of effectivenesscan be interpreted Effectively used. In conclusion, based on the assessment and expert input and the results of the field trial of the Android-Based Learning Media Application as a learning medium, it has been tested for feasibility, excellence, and can be used in the learning process in Creative Products and Entrepreneurship subjects in class XII TKJ 2 SMKN 8 Padang.